Knowledge, Perceptions and Attitudes Toward HPV Vaccination: A Survey on Parents of Girls Aged 11-18 Years Old in Greece - Panagiota Naoum; Kostas Athanasakis; Dimitris Zavras; John Kyriopoulos; Elpida Pavi (Frontiers Media S.A., 2022)
ObjectiveTo investigate knowledge, perceptions and practices of parents of girls aged 11-18 years old in Greece toward HPV vaccination, and determine which factors are associated with parents' decision to vaccinate their daughters.MethodsA close-end questionnaire was constructed and telephone interviews were conducted upon informed consent. The sample was random, national, stratified by geographic region and representative of the general population of parents of girls aged 11-18. The data collected include: general knowledge, attitudes and perceptions concerning HPV and HPV vaccine, information regarding their daughters' HPV vaccination, and sociodemographic characteristics. Statistical analysis included descriptives and a logistic regression model to investigate which factors are associated with HPV vaccination.ResultsOverall, 1,000 parents participated in the study, 99.4% of which knew what HPV is and 98.8% knew there is a vaccine available against HPV. Furthermore, 47% of the parents stated that their daughters had been vaccinated against HPV, while further analysis revealed that only 35% had received all the recommended doses. In the logistic regression analysis, the following variables had a statistically significant association with HPV vaccination: perceived ease of contracting HPV (OR = 1.105), level of trust in medical profession regarding information on prevention (OR = 1.205), overall perception regarding importance of children's vaccination (OR = 0.618), internet/social media as a source of parent information regarding HPV (OR = 0.886), participant (parent) age (OR = 1.125), and daughter's treating physician's recommendation for HPV vaccination (OR = 7.319).ConclusionsHPV vaccination coverage is still suboptimal. Comprehension of the obstacles toward this goal is important and the role of healthcare professionals is crucial to increase acceptance.